Xanthones from the stem bark of Garcinia nigrolineata - Rukachaisirikul V. (2014)
Nine xanthones, nigrolineaxanthones A-1, together with nine known xanthones, were isolated from the crude methanol extract of the stem bark of Garcinia nigrolineata; two of which have previously been reported as synthetic xanthones. The structures were elucidated by analysis of spectroscopic data, especially using 1D and 2D NMR spectroscopic data. © 2003 Elsevier Ltd. All rights reserved.